PKM KEMAMPUAN MERANCANG DESAIN INSTRUKSIONAL - Susanto, Ratnawati; Syofyan, Harlinda; Agustina, Noni; Anwar, Nizirwan; Fikri, Ahmad Dzaki; Febryna, Nurul; Pandini, Intan; Mawarni, Mawarni; Nisa’I, Siti Haerotun; Nisa, Mahwar Alfan; Oktafiani, Oktafiani (Universitas Esa Unggul, 2022)
Teachers are learning designers who have roles and functions to provide learning experiences that are able to optimize the potential of students to become competencies. The purpose of PKM is to strengthen the internal capacity of schools through a focus on empowering teachers to develop the ability to design Instructional Designs. through PKM Instructional Design Development to address partner problems that focus on: (1) optimizing the ability to design learning (instructional design), (2) understanding and application of design (design) and learning technology, (3) pedagogical abilities that are not monotonous and varied, (4) mastery of knowledge content to facilitate competency profiles of students who have critical thinking and problem solving, communication, collaborative and innovative skills. The method in implementing the stages and activity steps uses socialization, training, coaching, self-evaluation, reflective, exploration, practice, simulation, sharing knowledge and experiences. The activity stages are: (1) pre-conditioning (Practice & Pre-test) stage, (2) Socialization stage (FGD), (3) Competency and Coaching Improvement and Empowerment stage, (4) Measurement and Evaluation stage. The results of PKM are: (1) Increased knowledge and skills in the ability to design instructional design with 75% of teachers and an effectiveness level of 75%, and (2) 75% of teachers give an opinion on a questionnaire that community service programs are on average at the level of effectiveness 75%.Keywords: Instructional Design, Initial Behavior Analysis, Assessment Instruments, Learning Materials, Learning Objectives